SUFFICIENCY ECONOMY APPLICATION FOR IMPROVING THE QUALITY OF LIFE TO RAISE INCOME AND THE WELL-BEING OF THE ELDERLY FAMILIES IN PHETCHABURI PROVINCE - Chairum, Panus; Suwanboon, Pattariya; Kongmian, Ketsarin (Journal of MCU Phetchaburi Review, 2023)
The objectives of this research article were to: 1) study the quality of life and well-being of elderly families in Phetchaburi Province, 2) promote the development of quality of life to raise income and the well-being of elderly families in Phetchaburi Province, and 3) try out the activity model for developing the quality of life to raise income and the well-being of elderly families in Phetchaburi Province. The mixed research methodology was applied in this study. The 60 samples were the elderly. The research tools were a preliminary data survey form, a questionnaire, an interview form, and focus group discussion on organizing activities to raise the income of the elderly. The data were analyzed by using percentage and content discussion in descriptive form. The research results revealed that the elderly’s quality of life and family well-being were at a high level after organizing the following activities: 1) Inventing household appliances from local materials of the elderly in Ban Rahan Noi, Tamru Subdistrict, Ban Lat District, 2) Planting chemical-free vegetables on the fence along footpath at Ban Hua Thung - Thung Prao Phatthana, Tha Yang Sub-district, Tha Yang District, and building vegetable gardens of the members in each household in Ban Khlong Lat, Bang Tabun Subdistrict, Ban Laem District, and 3) Producing trash bins for separating household waste at Ban Sam Reun, Tha Takhro Subdistrict, Nong Ya Plong District. All 4 activities were based on the concept of sufficiency economy that could reduce expenses, increase income, and contribute good results according to the group’ needs. The research finding revealed that the elderly mainly had a sufficiency economy lifestyle and the ability to manage income-raising activities by reducing expenses and increasing income, resulting in the improvement of the elderly’s quality of life and well-being according to the principles of living based on the concept of sufficiency economy in normal and critical situations.